Nivel de conocimientos y factores sociodemográficos de las enfermeras en el manejo de ventilador mecánico en la unidad de cuidados intensivos - Llerena Otiniano, María Isabel (2017)
This research study aimed to determine the relationship between the level of knowledge and the sociodemographic factors of nurses in the management of mechanical ventilator in the Intensive Care Unit (U.C.I.) in Hospital Belen of Trujillo 2016. It is quantitative study, cross-sectional; with design descriptive - correlational. The sample consisted of 10 nurses working in the U.C.I. in Hospital of Trujillo who met the inclusion and exclusion criteria. For the collection of data, two instruments were used: The survey of the level of knowledge of the nurse in the management of mechanical ventilator and Questionnaire on sociodemographic factors. For the analysis of correlation of the variables was used statisticians eta, gamma and Fisher exact test, with a level of significance of α= 0.05. The results indicate that 80% of nurses have a level of acceptable knowledge in the management of mechanical ventilator and 20% has a level not acceptable; in relation to the sociodemographic factors of the nurse, it was found that 50% of nurses has less than 5 years of service in the U.C.I., 70 % of 11 to 13 years as a nurse and 70% have a title of specialty as a nurse in intensive care. It was also found that the age is related directly with the level of knowledge, given that the value of the coefficient eta exceeds 0.80, demonstrating that with increasing age of the nurse there is greater knowledge, however the years of experience in U.C.I., years of service as a nurse and title of specialty is not related statistically with the level of knowledge in the management of the mechanical ventilator in the U.C.I.